Two new bee species (Hymenoptera) from Bogotá city (Colombia) - GONZALEZ, VICTOR H. (Revista Colombiana de Entomología, 2006)
Two new bee species are described from the city of Bogotá (Colombia) whose biology is currently under study, in order to make the names available and facilitate the divulgation of this information. Males and females of the following species are described and illustrated: Lasioglossum (Dialictus) urbanus (Halictidae, Halictini) and Megachile (Cressioniella) amparo (Megachilidae, Megachilini).